Decolonising and Islamicising the study of English Literature: an argument for a comparative paradigm - Mohd Ramli, Aimillia (2012)
The study of English Literature was first introduced during the late eighteenth century in order to consolidate the superiority of British culture in comparison to the cultures of the colonised people. In the postcolonial period of the twentieth century, the continuation of the study of English literature had mainly been justified by Western liberal humanism’s belief that canonical works in English literature display universal values that should be cultivated in the minds of readers regardless of their nationality and ethnicity. The advent of theory in the last few decades, however, has meant the introduction of critical theories into the study of English literature. All of these approaches, both the humanistic model of universal values and critical theories in the study of English literature, pose a problem for Muslim academicians who view their personal belief in Islam as being at odds with these secular approaches. To counter this problem, this paper will suggest the use of a comparative paradigm that will juxtapose and compare between the Tawhidic framework of Islamic literature and the above-mentioned Western approaches in courses that study English literature. It will suggest a new reading of English literature from an Islamic perspective and framework.